A study of the mechanical properties of cement bonded coco excelsior board for use as a construction material - Lim, Winnifred H.
Wood-cement composite has great prospects in tropical and developing countries like ours. It is because of its weather durability, incombustibility and low cost that makes this a good alternative to other conventional types of building materials. However, the technological information available is limited. It is yet to be exploited to our fullest advantage. This study of the mechanical properties of Cement Bound Coco Excelsior Board (CBCEB) for use as a structural material in low-cost housing construction could make possible the use of our limitless agricultural waste products such as coconut palm wood. However, there are several factors that would ultimately determine its economy of use and the composite's ability to serve the purpose it was mae for. First, is the uncertainty caused by the coco wood extractives on the complete hydration of cement. Secondly, the material mixing proportions and lastly, the board's density. In order to fully determine the compatibility of coco wood with cement and the potential of producing low-cost structural panels, the following were taken into consideration: 1. The suitability of using some chemical additives on coco-wood-cement mix, among those tested were calcium chloride, aluminum sulfate and Houston-466. 2. The influence of varying material mixing proportions (e.g. wood/cement ration and water/cement ratio) 3. The effect of different board densities.